Sistem Pendukung Keputusan Pemberian Bantuan Dana Miskin pada Kabupaten Karo Menggunakan Metode AHP - Colia, Chandra; Sitorus, Lamhot (LPPM UNIKA Santo Thomas Medan, 2018)
The Family Hope Program (PKH) is intended to build a system of protection for the poor. In PKH, assistance given to very poor households is then obliged to send their children to school, conduct health checks including nutritional checks and immunization for toddlers and check the womb for pregnant women. In the short term, this assistance is expected to help reduce the burden of expenditure, while the long term is expected to break the chain of poverty between generations. Example: Jamkesmas, Apras (Pre-School Children, Toddler Children) The implementation of PKH carried out also by the Social Service Office in Karo Regency is still inadequate to provide assistance for poor funds, so that the system will be built using the AHP method. process or enter each specified condition or criteria and the weight that has been determined for each criterion into the system easily and quickly and make the report faster